Assessment of disease control in allergic rhinitis. Issue 1 (18th February 2013) - Demoly, Pascal; Calderon, Moises A; Casale, Thomas; Scadding, Glenis; Annesi‐Maesano, Isabella; Braun, Jean‐Jacques; Delaisi, Bertrand; Haddad, Thierry; Malard, Olivier; Trébuchon, Florence; Serrano, Elie
Abstract: The Allergic Rhinitis and its Impact on Asthma (ARIA) initiative has had a significant impact, by raising awareness of allergic rhinitis (AR) and improving the diagnosis and treatment of AR sufferers. ARIA classifies the severity of AR as "mild" or "moderate/severe" on the basis of "yes"/"no" answers to four questions. This two‐point classification has been criticized as providing little guidance on patient management; patients with "mild" AR are unlikely to consult a physician, whereas the group of patients with "moderate/severe" seen by specialists is heterogeneous. These perceived shortcomings have prompted attempts to improve the ARIA classification or, by analogy with the Global Initiative for Asthma (GINA), adopt approaches based on "disease control" in AR. Even though "disease severity", "disease control" and "responsiveness to treatment" are different (albeit related) metrics, they are not mutually exclusive. Currently, there is no single, accepted definition, but we propose that "disease control" in AR can combine (i) measurements of the severity and/or frequency of daily or nocturnal symptoms, (ii) impairments in social, physical, professional and educational activities, (iii) respiratory function monitoring and (iv) exacerbations (e.g. unscheduled medical consultations and rescue medication use). Although control‐based classifications have a number of limitations (e.g. their dependence on treatment compliance and the patient's psychological status), these instruments could be used as an adjunct to the ARIA severity classification and regional practice parameters. Here, we assess the strengths and weaknesses of the current two‐level ARIA classification, analyze published proposals for its modification and review the literature on instruments that measure AR control. We conclude that there is a need for research in which severity is compared with control in terms of their effects on patient management.